Health hazards resulting from exposure to zinc and its inorganic compounds in industry - Daria Pakulska; Sławomir Czerczak (Nofer Institute of Occupational Medicine, 2017)
This article deals with health risks resulting from exposure to zinc and its inorganic compounds in industry. The main source of zinc exposure are fumes generated during thermal and chemical processes, mainly zinc oxide fume formed by immediate oxidation of metallic zinc vapor formed during high-temperature processes, as well as dust generated during the mechanical processing of zinc-containing materials. It is recognized that zinc ions are responsible for health effects of exposure to dust/fumes of the majority of zinc compounds, and the final effect of exposure depends on the degree of dispersion of dusts/fumes suspended in the air. Since the effects of exposure depends on the particle size, occupational exposure limits have began to be established separately for respirable and inhalable fractions. A critical effect of acute exposure to respirable fraction is a "fume fever" which in chronic exposure occurs as an effect associated with recurrent symptoms of acute poisoning. Impaired lung function and asthma symptoms are considered to be the main effects of exposure to inhalable fraction. Due to the limited number of the available data it is not possible to assess carcinogenicity, reproductive toxicity and teratogenicity of zinc and its compounds. The aim of the study was to analyze the major health hazards resulting from occupational exposure to zinc and its inorganic compounds in the context of their physico-chemical properties, a wide range of applications and occupational exposure data. Med Pr 2017;68(6):779-794